ELECTROKINETIC PHENOMENA - Harold A. Abramson (1933)
By assuming that the electric charge of proteins is primarily determined by the hydrogen ion activity of the medium, and by making corrections when necessary for the effect of salt, it is possible to derive a simple relationship between the electric mobility of proteins and the effective reciprocal thickness of the electric double layer. The decrease in electric mobility of proteins in solutions is readily predicted for gelatin in acetate buffers and for egg albumin in the presence of the alkali halides, of acetate buffers, and of hydrochloric acid on the basis of the assumptions made.